Mini-incision versus standard incision total hip arthroplasty regarding surgical outcomes: a systematic review and meta-analysis of randomized controlled trials. - Chang-Peng Xu; Xue Li; Jin-Qi Song; Zhuang Cui; Bin Yu (PLoS ONE, 2013)
Purpose It remains controversial whether mini-incision (MI) benefits patients in total hip arthroplasty (THA). We performed a meta-analysis of randomized controlled trials (RCTs) to assess the effects of MI on surgical and functional outcomes in THA patients. Methods A systematic electronic literature search (up to May 2013) was conducted to identify RCTs comparing MI with standard incision (SI) THA. The primary outcome measures were surgical and functional outcomes. According to the surgical approach taken, MI THA patients were divided into four subgroups for sub-group meta-analysis. Standardized mean differences (SMDs) or risk differences (RDs) with accompanying 95% confidence intervals (CIs) were calculated and pooled using a fixed-effect or random-effect model according to the heterogeneity. Results A total of 14 RCTs involving THA 1,174 patients met the inclusion criteria. The trials were medium risk of bias. The overall meta-analysis showed MI THA reduced total blood loss (95% CI, -201.83 to -21.18; p=.02) and length of hospital stay ( 95% CI, -0.67 to -0.08; p=.01) with significant heterogeneity. However, subgroup meta-analysis revealed posterior MI THA had perioperative advantages of reduced surgical duration ( 95% CI, -8.45 to -2.67; P<.001), less blood loss ( 95% CI, -107.20 to -1.73; P=.04) and shorter hospital stay ( 95% CI, -0.74 to -0.06; p=.002) with low heterogeneity. There were no significant differences between MI and SI THA groups in term of pain medication dose, functional outcome (HHS), radiological outcome or complications (P>.05, respectively). Conclusions Although no definite overall conclusion can be arrived at on whether MI THA is superior to SI THA, posterior MI THA clearly result in a significant decrease in surgical duration, blood loss and hospital stay. It seems to be a safe minimally invasive surgical procedure without increasing the risk of component malposition or complications.